Utilization and Timing of Cystoscopy for Hematuria Evaluation by Advanced Practice Providers and Urologists - Hyman, Max J.; Skolarus, Ted A.; Cabral, Joshua; Shewmon, Kate; Bedziner, Moshe; Agarwal, Piyush K.; Modi, Parth K. (Urology (Ridgewood, N.J.), 2024)
To characterize differences between urologists and advanced practice providers (APPs) in the utilization of cystoscopy for hematuria. We identified patients initially evaluated for hematuria by a urologist or urology APP between 2015 and 2020 in the MarketScan Research Databases. We determined whether they received a cystoscopy within 6 months of their urology visit and the number of days until cystoscopy. We used multivariable regression to analyze the association between these outcomes and whether the urology clinician was an advanced practice registered nurse (APRN), physician assistant (PA), or urologist. We identified 34,470 patients with microscopic hematuria and 17,328 patients with gross hematuria. Patients evaluated by urologists more often received a same-day cystoscopy than those evaluated by APPs (13% vs 5.8%). The odds that patients evaluated for microscopic and gross hematuria received a cystoscopy were 46.2% and 26.2% lower, respectively, if they were evaluated by an APRN vs a urologist. Patients seeing an APRN for microscopic and gross hematuria also waited approximately 7 and 14 days longer for their cystoscopy, respectively. No differences were observed for patients evaluated by PAs vs urologists. Patients evaluated for hematuria by an APRN were less likely to receive a cystoscopy and had a longer wait until the procedure compared to those evaluated by a urologist; however, no differences were observed between PAs and urologists. Better understanding APP integration into urology clinics is warranted.